2013
DOI: 10.1080/09503153.2013.775236
|View full text |Cite
|
Sign up to set email alerts
|

Through the Eyes of Ex-Foster Children: Placement Success and the Characteristics of Good Foster Carers

Abstract: Randle, M. (2013). Through the eyes of ex-foster children: placement success and the characteristics of good foster carers. Practice: social work in action, 25 (1), 3-19. Through the eyes of ex-foster children: placement success and the characteristics of good foster carers AbstractMost research focusing on foster placement success or the characteristics of good foster carers is based on the opinions of people currently involved in the foster care system, such as foster carers, social workers or children in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 15 publications
1
11
0
1
Order By: Relevance
“…In Australia, the number of children in out-of-home care has reached 43 000, a rate of 8.1 children per 1000 and an increase of 20% between 2010 and 2014 (Australian Institute of Health and Welfare, 2015). This upward trend is mirrored in other countries around the world including, for example England, with foster placements up 9% between 2010 and 2015 (Zayed & Harker, 2015), the USA, up 5% between 2012 and 2014 (Children's Bureau, 2015) and Ireland, up 15% between 2010and 2013(Department of Health, 2014.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In Australia, the number of children in out-of-home care has reached 43 000, a rate of 8.1 children per 1000 and an increase of 20% between 2010 and 2014 (Australian Institute of Health and Welfare, 2015). This upward trend is mirrored in other countries around the world including, for example England, with foster placements up 9% between 2010 and 2015 (Zayed & Harker, 2015), the USA, up 5% between 2012 and 2014 (Children's Bureau, 2015) and Ireland, up 15% between 2010and 2013(Department of Health, 2014.…”
Section: Introductionmentioning
confidence: 98%
“…These negative consequences include lower levels of behavioural well-being (Rubin et al, 2007), higher mental health service use (Rubin et al, 2004) and reduced resilience and psychosocial development (Harden, 2004). Stability within a foster placement has been cited as critical for placement success (Newton et al, 2000), both in terms of optimizing the longer-term outcomes for the child and also for creating feelings of security and belonging for the child while in the placement (Randle, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Some psychological constructs, such as concern for children (Buehler et al, 2003;Harkin and Houston, 2016), genuine desire to help the child and include them as part of the family (Randle, 2013), a capacity to set boundaries, maintain consistency in routine, yet demonstrate flexibility (Rock et al, 2015), have been related to improved placement outcomes. In particular, a carer's ability to understand why a child responds to circumstances the way they do (Buehler et al, 2003) and to not reject the child on the basis of their behaviour, is a key factor (Sinclair and Wilson, 2003;Sinclair et al, 2005).…”
Section: The Target Segment Of High Performing Foster Carersmentioning
confidence: 99%
“…The Northwest Alumni study (Pecora et al, 2010), which interviewed 479 alumni of foster care in three American agencies, identified a link between feeling loved and being involved with the foster family and doing well in several outcome domains. Randle (2013) conducted a qualitative study of eleven people who were over 18 and had been in foster care as children. Her interviews with those people indicated that a successful placement was one where they felt wanted by the carers and other people in the same household.…”
Section: Who Needs To Be Attracted and Recruited To Promote Positive mentioning
confidence: 99%